Assessing Information Search by Task Outcome - Vakkari, Pertti (Journal of Information and Knowledge, 2023)
People do not search information as such but seek to get a job done or to manage a situation by the help of search results. Therefore, the ultimate goal of information search is to advance task performance. It should be evaluated accordingly, i.e. by its contribution to task outcome. This implies an extended notion of search process, which also covers the use of information in search results for task outcome. For measuring the effect of search to task outcome we propose both indirect and direct indicators which measure search success.